Annual Research Review: A meta‐analytic review of worldwide suicide rates in adolescents. (1st August 2019) - Glenn, Catherine R.; Kleiman, Evan M.; Kellerman, John; Pollak, Olivia; Cha, Christine B.; Esposito, Erika C.; Porter, Andrew C.; Wyman, Peter A.; Boatman, Anne E.
Abstract : Suicide is a leading cause of death among youth worldwide. The purpose of the current review was to examine recent cross‐national trends in suicide mortality rates among 10‐ to 19‐year‐olds. This study extracted suicide mortality data from the World Health Organization's (WHO) Mortality Database for the most recent year (since 2010) from any country with available high‐quality data (as defined by the WHO's guidelines). Data on access to lethal means (firearms, railways) and measures of economic quality (World Bank Income Group) and inequality (Gini coefficients) were obtained from publicly available data sources. Cross‐national suicide mortality rates in youth were heterogeneous. The pooled estimate across all ages, sexes, and countries was 3.77/100, 000 people. The highest suicide rates were found in Estonia, New Zealand, and Uzbekistan. Suicide rates were higher among older compared with younger adolescents and higher among males than females. The most common suicide methods were hanging/suffocation and jumping/lying in front of a moving object or jumping from a height. Firearm and railway access were related to suicide deaths by firearms and jumping/lying, respectively. Economic quality and inequality were not related to overall suicide mortality rates. However, economic inequality was correlated with a higher ratio of male:female suicides. This study provides a recent update of cross‐national suicide trends in adolescents. Findings replicate prior patterns related to age, sex, geographic region, and common suicide methods. New to this review are findings relating suicide method accessibility to suicide mortality rates and the significant association between income inequality and the ratio of male:female suicide. Future research directions include expanding the worldwide coverage to more low‐ and middle‐income countries, examining demographic groupings beyond binary sex and to race/ethnicity within countries, and clarifying factors that account for cross‐national differences in suicide trends. Abstract : Read the Commentary on this article at doi: 10.1111/jcpp.13174